2007
DOI: 10.5194/angeo-25-283-2007
|View full text |Cite
|
Sign up to set email alerts
|

Pickup protons at quasi-perpendicular shocks: full particle electrodynamic simulations

Abstract: Abstract. We have performed 3 one-dimensional full particle electromagnetic simulations of a quasi-perpendicular shock with the same Alfvén Mach number M A ∼5, shock normal-magnetic field angle Bn =87 • and ion and electron beta (particle to magnetic field pressure) of 0.1. In the first run we used an ion to electron mass ratio close to the physical one (m i /m e =1024). As expected from previous high mass ratio simulations the Modified Two-Stream instability develops in the foot of the shock, and the shock pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…We see that the solar wind ion dynamics proceed essentially as in the absence of the pickup ions, whereas the pickup ions form an stationary extended foot starting ∼ 4(c/Ω ci ) upstream. This phenomenon has already been demonstrated by a good deal of hybrid and PIC simulations Liewer et al 1993;Lipatov and Zank 1999;Chapman et al 2005; Lee et al 2005;Matsukiyo et al 2007;Wu et al 2009;Matsukiyo and Scholer 2011). In this subsection, we will clarify why the low percentage pickup ions can not suppress the self-reformation of the shock front by analyzing the cross shock electric field which play a key role in the reflection of incident ions.…”
Section: Effect Of Low Percentage Pickup Ions On the Cross Shock Elecmentioning
confidence: 99%
“…We see that the solar wind ion dynamics proceed essentially as in the absence of the pickup ions, whereas the pickup ions form an stationary extended foot starting ∼ 4(c/Ω ci ) upstream. This phenomenon has already been demonstrated by a good deal of hybrid and PIC simulations Liewer et al 1993;Lipatov and Zank 1999;Chapman et al 2005; Lee et al 2005;Matsukiyo et al 2007;Wu et al 2009;Matsukiyo and Scholer 2011). In this subsection, we will clarify why the low percentage pickup ions can not suppress the self-reformation of the shock front by analyzing the cross shock electric field which play a key role in the reflection of incident ions.…”
Section: Effect Of Low Percentage Pickup Ions On the Cross Shock Elecmentioning
confidence: 99%
“…Herein, the shock is produced by the injection method as in previous PIC simulations ( Lee et al 2005;Matsukiyo et al 2007;Yang et al 2012a). In order to reproduce self-consistently the impacts of PUIs, three particlespecies are introduced within our PIC code: electrons, SWIs, and PUIs.…”
Section: Simulation Modelmentioning
confidence: 99%
“…In contrast to hybrid simulations, both electron and ion populations are taken into account as individual particles in PIC simulations, and the electrostatic potential jump at the ramp with awidth ofa few electron inertial lengths has been self-consistently reproduced (Matsukiyo et al 2007). Matsukiyo & Scholer (2011) have investigated the impact of PUIs on the TS by using a 1D PIC code.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [2009] developed a modified Rankine-Hugoniot model that included pickup ions to interpret the hybrid simulations. Wu et al [2010] showed that specular reflection of ions [Zank et al, 1996] by the electric field normal to such a shock is not necessary for an initial energy gain of pickup ions; rather, the large gyroradius of these ions enables some of them to return upstream where they gain substantial energy from the motional electric field as they gyrate in the foot Chapman et al, 2005;Matsukiyo et al, 2007]. Further, Wu et al [2010] demonstrated that faster solar wind flows lead to increased fluxes of ions in the tails of their velocity distributions, consistent with energetic neutral atom observations from IBEX [Funsten et al, 2009].…”
Section: Previous Simulationsmentioning
confidence: 99%
“…Although onedimensional PIC simulations have been applied to the termination shock Chapman et al, 2005;Matsukiyo et al, 2007], such computations require that the electron dynamics be followed in detail. This restricts such calculations to relatively short times and, typically, to one spatial dimension.…”
Section: Previous Simulationsmentioning
confidence: 99%